An accurate "metal pre-buried" strategy for constructing Ni–N2C2 single-atom sites with high metal loadings toward electrocatalytic CO2 reduction. Issue 47 (23rd November 2022) - Liu, Xian; Liao, Luliang; Xia, Guomin; Yu, Fuqing; Zhang, Guangyao; Shu, Minxing; Wang, Hongming
Abstract : Ni–N2 C2 SACs were obtained by the cleavage of Ni–O bonds and formation of Ni–C bonds. Abstract : Although single-atom catalysts (SACs) dispersed on N-doped carbon supports with the M–N2 C2 configuration have high application potential in electrocatalysis, combining this configuration with high metal loadings remains a considerable challenge. In this study, a Ni-salen polymer with a confined metal position and precise coordination mode (Ni–N2 O2 ) serves as a precursor, which not only suppresses the aggregation of metal atoms but also promotes the creation of Ni–N2 C2 centers owing to the cleavage of Ni–O bonds and formation of Ni–C bonds during high-temperature pyrolysis. A Ni–N2 C2 SAC with a metal loading of 9.15 wt% exhibits excellent catalytic performance for the CO2 electroreduction to CO with a faradaic efficiency (FECO ) of 98.7% at −0.82 V vs. the reversible hydrogen electrode (RHE). Theoretical calculation data have further demonstrated that the modified electronic structure of the Ni–N2 C2 -p model is responsible for its high intrinsic activity. This work proposes a new strategy for maintaining both the precise Ni–N2 C2 structure and high metal loading.